Swift: poetical repurposer - Cox, O (Duke University Press, 2024)
Poets steal. Or, to put it politely, borrow. Jonathan Swift preposterously claimed to do neither. He did so ironically, however, by lifting a line from John Denham's On Mr Abraham Cowley and putting it into the mouth of a hypothetical, ignorant critic elegizing “Swift”: Denham's “what he wrote was all his own” becomes Swift's “what he writ was all his own” (1–2). Daniel Cook's book, Reading Swift's Poetry, opens with this beautiful illustration of Swift's metapoetic tricksiness, which serves as an apt base from which Cook examines Swift's chronic filching from the poetic archive. The question of how an author makes new from old (stale genres, tropes, clichés, etc.) dogged Swift throughout his literary career—as, of course, it has many authors before and since—and Cook charts Swift's borrowings (largely) chronologically from his early poetry through to his final works. In addition to Swift's intertextuality, Cook examines other foundational elements...